Dysfunctional exclusion within Christian/Muslim relationships in Gombe state, Nigeria : a co-pathic approach - Tuduks, Oholiabs D. (Stellenbosch : Stellenbosch University, 2015)
Thesis (MTh)--Stellenbosch University, 2015.